Regarding research and teaching staff professional development as an integral part of providing quality training for future professionals with higher education - Nataliia, Kalashnik; Adamovych, Anastasiia; Адамович, Анастасія Євгенівна; Адамович, Анастасия Евгеньевна; Marianna, Barus; Nataliia, Goliardyk (My University, 2021)
EN: In the article, the authors emphasize that the content and forms of the teachers’ professional development should be diversified taking into account the competence level, experience in teaching specific subjects and as well as pedagogical skills. The content of long-term professional development should correspond to the psychological and pedagogical sciences latest achievements, vocational education, innovative processes, higher education institutions program goals, teachers’ individual educational needs and be implemented on the basis of diagnostic, competence and practice-oriented approaches. It was concluded that it is necessary to revise the current system and create a continuous one of scientific and pedagogical staff professional development, which would take into account experience and current trends worldwide, in leading European countries and national characteristics too. It should be flexible, dynamic, and adequate to the specific educational institutions requirements and consider the teachers’ level of professional competence. UK: У статті автори акцентують увагу на тому, що зміст та форми підвищення кваліфікації викладачів повинні урізноманітнюватися з урахуванням рівня професіоналізму, досвіду викладання дисциплін та педагогічної майстерності. Зміст довгострокового підвищення кваліфікації має відповідати новітнім досягненням психолого-педагогічних наук, професійної освіти, інноваційним процесам, програмним цілям закладів вищої освіти, індивідуальним освітнім запитам педагогічних працівників та реалізуватись на основі діагностичного, компетентнісного та практико-спрямованого підходів. Дійшли висновків у необхідності перегляду чинної і створенні неперервної системи підвищення кваліфікації науково-педагогічних кадрів, яка б враховувала сучасні тенденції, досвід провідних країн Європи та світу й національні особливості. Вона має бути гнучкою, динамічною, адекватною вимогам конкретних освітніх закладів і враховувати рівень професійної компетентності викладачів.
Щодо підвищення кваліфікації науково-педагогічних працівників, як невід’ємної складової забезпечення якісної підготовки майбутніх фахівців з вищою освітою
Keywords: advanced training; scientific and pedagogical workers; professional competence; підвищення кваліфікації; науково-педагогічні працівники; професійна компетентність